2019
DOI: 10.4103/jfmpc.jfmpc_144_19
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of India's Swachh Bharat Mission – Clean India Campaign on acute diarrheal disease outbreaks: Yes, there is a positive change

Abstract: Background: Enough evidence exists to attribute the occurrence of diarrheal disease outbreaks due to open defecation practice and unsafe sanitation methods. Open defecation enables pathogens such as virus, bacteria, and protozoa to infect humans by means of fecal–oral transmission methods through contaminated fluids, water, and fomites. To curb the malefic effects of open defecation, the Indian government had initiated pro sanitation program namely Swachh Bharat Mission (SBM) in 2014. SBM became t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 24 publications
1
29
0
Order By: Relevance
“…We recognize there is no one-size-fits-all for delivering these essential services [ 63], but governments should explore immediately delivering water trucks, sanitizing stations, and portable toilets. Communities should be consulted, along with local officials, and municipal and national policies should be prepared to develop plans that provide clean water and safe, hygienic, and dignified toilets on a large scale, such as that of India's Swachh Bharat Abhiyan (SBA) or Clean India Mission [64]. (6) Immediate food assistance.…”
Section: Introductionmentioning
confidence: 99%
“…We recognize there is no one-size-fits-all for delivering these essential services [ 63], but governments should explore immediately delivering water trucks, sanitizing stations, and portable toilets. Communities should be consulted, along with local officials, and municipal and national policies should be prepared to develop plans that provide clean water and safe, hygienic, and dignified toilets on a large scale, such as that of India's Swachh Bharat Abhiyan (SBA) or Clean India Mission [64]. (6) Immediate food assistance.…”
Section: Introductionmentioning
confidence: 99%
“…Sub-optimal increases in coverage may limit the health benefits of sanitation programs [5][6][7][8]. While there is some consensus on the overall principles needed to achieve and sustain universal sanitation coverage [9], there is little rigorous evidence of successful programs at scale [10]. Context plays an important role in determining the implementation approach, so evidence of success and challenges of cross-country programs could support the rural sanitation and hygiene sector in achieving universal coverage.…”
Section: Introductionmentioning
confidence: 99%
“…Since 1986, the Government of India has taken several initiatives to improve the sanitation in the country. 10 It initiated the Central Rural Sanitation Programme in 1986, which is considered as a failure because the reality on the ground did not match the requirements for success. This was followed by the total sanitation campaign (TSC) launched in the year 1999, which was supposed to have been modified based on key lessons that were learned from previous program.…”
Section: Sanitation Program (S ) O F Government O F Indiamentioning
confidence: 99%
“…• The Indian Space Research Organization (ISRO) center at Jodhpur in partnership with others from Hyderabad and other places has carried out an in-depth country-wide study on the impact of SBM using Integrated Disease Surveillance Project (IDSP) data from 2010 to 2018. 10 The year-wise count of acute diarrheal disease (ADD) outbreaks, summer and July season peaks, the total number of toilets constructed under SBM, and the total villages that gained the status of open defecation free were analyzed. It was observed that the years 2017 and 2018 recorded the lowest number of total ADD outbreaks.…”
Section: Sanitation Program (S ) O F Government O F Indiamentioning
confidence: 99%
See 1 more Smart Citation